Spectroscopic and electrochemical characterization of nanostructured optically transparent carbon electrodes - Benavidez, Tomás Enrique (2013)
The present paper describes the results related to the optical and electrochemical characterization of thin carbon films fabricated by spin coating and pyrolysis of AZ P4330-RS photoresist. The goal of this paper is to provide comprehensive information allowing for the rational selection of the conditions to fabricate optically transparent carbon electrodes (OTCE) with specific electrooptical properties. According to our results, these electrodes could be appropriate choices as electrochemical transducers to monitor electrophoretic separations. At the core of this manuscript is the development and critical evaluation of a new optical model to calculate the thickness of the OTCE by variable angle spectroscopic ellipsometry. Such data were complemented with topography and roughness (obtained by atomic force microscopy), electrochemical properties (obtained by cyclic voltammetry), electrical properties (obtained by electrochemical impedance spectroscopy), and structural composition (obtained by Raman spectroscopy). Although the described OTCE were used as substrates to investigate the effect of electrode potential on the real-time adsorption of proteins by ellipsometry, these results could enable the development of other biosensors that can be then integrated into various CE platforms.